2009
DOI: 10.4149/gpb_2009_02_105
|View full text |Cite
|
Sign up to set email alerts
|

New strategies for novel antibiotics: peptides targeting bacterial cell membranes

Abstract: Abstract. Membranes are targets of host defence or antimicrobial peptides, effector molecules of innate immunity that evolved in nature to contend with invaders as an active system of defence. The different physicochemical properties of the lipids found in biological membranes allow antimicrobial peptides to discriminate between bacterial and mammalian cell membranes. Such cationic amphipathic peptides will interact predominantly with negatively charged lipids exposed on the outer leaflet of bacterial cell mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 79 publications
1
116
0
2
Order By: Relevance
“…Many of these antibiotics are targeting the cell membrane and dissipate the membrane potential (33). Incubation of B. subtilis with the natural antibiotic nisin results in elongated cells and minicells, indicative of a malfunctioning Min system (34).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these antibiotics are targeting the cell membrane and dissipate the membrane potential (33). Incubation of B. subtilis with the natural antibiotic nisin results in elongated cells and minicells, indicative of a malfunctioning Min system (34).…”
Section: Discussionmentioning
confidence: 99%
“…The latter involve the production of AMPs that are synthesized in the fat body and subsequently secreted into the hemolymph [39,40]. In general, AMPs can serve as effective antibiotics or fungicides that mainly attack the cell envelope, especially the cell membrane and also affect intracellular targets of microorganisms which subsequently lead to cell death [41][42][43]. Several recent studies that reported the antimicrobial activity of the larvae hemolymph and maggot extract as well as of secretions, are promising for the development of new therapeutically valuable antibiotics, particularly in the defense of multi-resistant "super bugs" (e.g.…”
Section: Antimicrobial Peptides From H Illucens Larvaementioning
confidence: 99%
“…These specialized regions are referred to as lipid rafts and caveolae [10][11][12] . There are substantial differences in the phospholipid composition of bacterial and mammalian cell membranes, likely contributing to the preferential action of host defense molecules against bacterial targets [13][14][15] . Furthermore, lipids liberated from cellular membranes have been found to be strong modulators of inflammation.…”
Section: Biological Functions Of Lipidsmentioning
confidence: 99%